Smart Wake-Up: Revolutionizing Morning Alarms for the Modern Generation - Ashwin, Ashwin; Vijayalaxmi, Vijayalaxmi (International Journal of Industrial Engineering, Technology & Operations Management, 2024)
Developing an Android-based application for an alarm clock using the Android Studio IDE introduces a unique approach to addressing common issues with waking up on time. The primary feature of this application is designed to require users to physically move and walk a few steps to deactivate the ringing alarm. This functionality forces users to wake up fully, preventing them from repeatedly snoozing at the alarm and falling back asleep. The application is specifically tailored to assist students in maintaining a disciplined morning routine. Encouraging users to get out of bed promptly helps them prepare for their day, attend morning classes on time, and avoid skipping breakfast, essential for energy and focus throughout the day. In addition to its benefits for students, the application is equally valuable for working professionals who struggle with the habit of snoozing alarms repeatedly. It aims to instill a sense of punctuality and ensure they begin their day on schedule, contributing to better time management and productivity. This innovative solution addresses a widespread challenge by combining technology with behavioral motivation. It promotes healthier habits and ensures users start their day with momentum, making it a practical tool for anyone looking to improve their morning routine. With its user-friendly interface and purposeful design, the Android-based alarm clock application is poised to offer a reliable and engaging solution to an everyday problem, empowering individuals to take charge of their mornings effectively.